Application of Edible Coating Derived from Salacca Seed and Glucomannan on Red Chili (Capsicum annuum L.) - Evita Nugroho; Dian Kharisma Rahmawati; Vincentius Ferry; Ahmad Yumroni; Sri Rahayoe (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
Chili is a significant commodity in Indonesia, but its short shelf life often leads to supply shortages and price fluctuations. To address this, post-harvest processing techniques, such as applying edible coating, are employed. This coating forms a thin plastic-like layer on the surface of the product, inhibiting metabolism while ensuring safety for consumption. Therefore, this research aimed to assess the effect of edible coating comprised of salacca seed flour and glucomannan, both at room temperature and under cold storage conditions, on weight loss, hardness, and color, ultimately extending the shelf life of chili. Edible coating procedure involved using salacca sourced from the Sleman market, porang tuber from Gunung Kidul farmer, as well as aqua dest, glycerol, and 96% ethanol. Various concentrations of coating layers were tested, including 1% salacca seed flour, 5% salacca seed flour, 10% salacca seed flour, 0.4% glucomannan, and a non-coated control group. The result showed that the optimal treatment during storage at room and the cold temperature was achieved with a 0.4% glucomannan coating layer and 1% salacca seed flour coating layer. Based on evaluations of weight loss, hardness, and color, it could be concluded that both salacca seed flour and glucomannan can extend the shelf life of chili.